Traditional Fishing Gears and Methods of the Bodo Tribes of Kokrajhar, Assam - Basumatary, Nelson; Khangembam, Bronson Kumar (Fishery Technology, 2023)
Fish and fishery are an important part of the culture and tradition of many tribal communities of North East India including the Bodo tribes of Assam. The Bodos use varieties of unique traditional fishing gears and methods for fishing. Understanding and documenting such traditional knowledge systems are important to prevent them from vanishing with time. This paper aims to study and document the traditional fishing gears of Bodo tribes and their methods of operation. The study was conducted in six villages of Kokrajhar district, Assam, India from April 2021 to March 2022 through surveys including semi-structured questionnaires and personal interviews. Altogether 135 respondents participated in the study and 35 different fishing gears were recorded including the ones, which were previously not reported. They were categorized into impaling gears, hook & lines, and traps and pots. The natural resources and fish diversity were seen to influence the structure and design of gears in the study. The popularity and usage of some of the gears like Sahera, Baga, Borom Je and Dura Je were found declining, which may be attributed to increasing popularity of destructive fishing techniques like electric fishing, blast fishing and poisoning. This study will help in proper recognition, documentation and preservation of rich traditional knowledge on traditional fishing gears and methods of the region.